2020
DOI: 10.1029/2020gl089325
|View full text |Cite
|
Sign up to set email alerts
|

Poleward Shift of Northern Subtropics in Winter: Time of Emergence of Zonal Versus Regional Signals

Abstract: The Northern Hemisphere mid-latitudes will be exposed to hydroclimatic risk in next coming decades because the subtropical expansion. However, it is not clear when the anthropogenic signal will emerge from the internal climate variability. For this purpose, we investigate the time of emergence (ToE) of the hemispheric and regional shift of northern subtropical margins in the Max Planck Institute Grand Ensemble. For several indicators, the ToE of the poleward shift of Northern subtropical margin will not occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
(81 reference statements)
2
20
0
Order By: Relevance
“…The poleward extension of the Hadley Cell may result in the extension of these arid regions to higher latitudes. For example, reduced precipitation and more frequent droughts have been observed in the subtropics (e.g., Southern Australia, the Mediterranean region, and Northern China), which are linked to the expansion of Hadley Cell for the past few decades, e.g., [1,2] and others. The frequent extreme events of heat waves occurring in Europe in recent years are attributed to the poleward extension of the subtropical high due to the Hadley Cell expansion and the northward shift of the westerly jet in summer.…”
Section: What Is the Hadley Cell?mentioning
confidence: 99%
See 4 more Smart Citations
“…The poleward extension of the Hadley Cell may result in the extension of these arid regions to higher latitudes. For example, reduced precipitation and more frequent droughts have been observed in the subtropics (e.g., Southern Australia, the Mediterranean region, and Northern China), which are linked to the expansion of Hadley Cell for the past few decades, e.g., [1,2] and others. The frequent extreme events of heat waves occurring in Europe in recent years are attributed to the poleward extension of the subtropical high due to the Hadley Cell expansion and the northward shift of the westerly jet in summer.…”
Section: What Is the Hadley Cell?mentioning
confidence: 99%
“…In particular, the forced poleward shift of the storm track is most significant over the North Atlantic, which highlights the importance of a regional perspective when considering Hadley Cell width variations. More recent studies investigated the Hadley Cell edge based on the longitudinally varying methods and higher temporal resolution information [2,54]. For example, Martin et al [54] found significant contraction of the tropics over the eastern Pacific between 1981 and 2015, and slight but significant expansion in other region.…”
Section: Reasons For Discrepancy Among Trends In Hadley Cell Expansionmentioning
confidence: 99%
See 3 more Smart Citations